An Analysis on Factors That Influence Students’ Anxiety in Speaking English - Mahdalena Mahdalena; Asnawi Muslem (Research in English and Education Journal, 2021)
This research aims at exploring some theories and previous findings related to students' speaking anxiety and identifying the factors and the phenomena that influence students’ speaking anxiety as well as finding out the way students to anticipate reducing their anxiety while speaking English.This research used library research in nature. In conducting the research, the researcher used two theories as the framework of the study. The first theories used by Worde (2003) and the second theory was from Rajitha Alamelu (2019).  The researcher analysed this data using descriptive qualitative. The results of this research found that there were some influential factors that contribute to the students' anxiety in speaking English namely: speaking activities, inability to comprehend, pedagogical practices, error correction, fear of negative evaluation, external factors and internal factors. Meanwhile, several strategies from Kondo and Ying-Ling (2004)used toreduce students' anxiety in learning foreign languages, especially when appearing in front of the class, are preparation, relaxation, positive thinking, making friends, and resigning. Therefore, students are expected to be able to minimize their anxiety and improve their English skills.